2010
DOI: 10.1038/onc.2010.402
|View full text |Cite
|
Sign up to set email alerts
|

The orphan G protein-coupled receptor GPR55 promotes cancer cell proliferation via ERK

Abstract: GPR55 is an orphan G protein-coupled receptor that may be engaged by some lipid ligands such as lysophosphatidylinositol and cannabinoid-type compounds. Very little is known about its expression pattern and physio-pathological relevance, and its pharmacology and signaling are still rather controversial. Here we analyzed the expression and function of GPR55 in cancer cells. Our data show that GPR55 expression in human tumors from different origins correlates with their aggressiveness. Moreover, GPR55 promotes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
166
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(183 citation statements)
references
References 32 publications
14
166
1
Order By: Relevance
“…GPR55-mediated MAPK Signaling-Importantly, our findings demonstrate that LPI-induced ERK1/2 phosphorylation is controlled, at least in part, by ROCK, supporting the role for G␣ 12/13 in LPI signaling and indicating cross-talk between MAPK and Rho GTPases signaling, which is in line with Andradas et al (11). Such cross-talk may be communicated via the serine/threonine kinase Raf family, of which the expression level of the oncogene B-Raf in turn controls the stimulation of ROCK (60).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…GPR55-mediated MAPK Signaling-Importantly, our findings demonstrate that LPI-induced ERK1/2 phosphorylation is controlled, at least in part, by ROCK, supporting the role for G␣ 12/13 in LPI signaling and indicating cross-talk between MAPK and Rho GTPases signaling, which is in line with Andradas et al (11). Such cross-talk may be communicated via the serine/threonine kinase Raf family, of which the expression level of the oncogene B-Raf in turn controls the stimulation of ROCK (60).…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, GPR55-induced ERK1/2 phosphorylation regulates human cancer cell migration in vitro and proliferation in vivo (3,8,11). It also appears to govern the maintenance of persistent inflammatory pain (22,23).…”
Section: Studying the Pharmacology Of Gpr55 Using Alphascreenmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to their dramatic effects on the nervous, immune and other systems, recent studies have shown that various agonists of the classical cannabinoid receptors CB1 and CB2 possess antitumor effects, and have been approved to treat cancer or to eliminate the side effects of chemotherapy (Alexander et al, 2009;Oesch and Gertsch, 2009). Interestingly, in this issue of Oncogene, two groups demonstrated that GPR55 is expressed in various cancer types in an aggressivenessrelated manner and have a critical role in regulating cancer-cell proliferation (Andradas et al, 2011;Pin˜eiro et al, 2011).…”
mentioning
confidence: 99%